Transforming Education: The Role of Intercultural Teacher Training in the Integration of Foreign Immigrant Students (Innovaciones Educativas, 2024)
Interculturality in teacher education plays a fundamental role in the integration process of migrant students. Studies on the subject show that it is necessary to train teachers in interculturality from their initial training and on an ongoing basis. This will allow them to work with diverse classrooms in an equitable and quality manner, and also to develop more effective didactic planning that values students' knowledge. The manuscript introduces two concepts: interculturality and intercultural sensitivity. It then explains the concept of migration and its educational challenges. Based on all this, it presents the need to prepare teachers in interculturality in order to develop intercultural sensitivity. The conclusions are threefold: first, intercultural awareness should begin in higher education and implies a continuous learning process. Second, intercultural education provides teachers with the knowledge and skills needed to design their teaching strategies according to the needs, knowledge and context of the students. Third, interculturality enables teachers and students to learn from other cultures and to understand that society is diverse and multicultural.
Keywords: migration; cultural identity; intercultural education; intercultural communication; social justice; teacher training